A Review of the Global Burden, New Diagnostics, and Current Therapeutics for Amebiasis - Shirley, Debbie-Ann T; Farr, Laura; Watanabe, Koji; Moonah, Shannon (Open forum infectious diseases, 2018)
Amebiasis, due to the pathogenic parasite Entamoeba histolytica, is a leading cause of diarrhea globally. Largely an infection of impoverished communities in developing countries, amebiasis has emerged as an important infection among returning travelers, immigrants, and men who have sex with men residing in developed countries. Severe cases can be associated with high case fatality. Polymerase chain reaction–based diagnosis is increasingly available but remains underutilized. Nitroimidazoles are currently recommended for treatment, but new drug development to treat parasitic agents is a high priority. Amebiasis should be considered before corticosteroid therapy to decrease complications. There is no effective vaccine, so prevention focuses on sanitation and access to clean water. Further understanding of parasite biology and pathogenesis will advance future targeted therapeutic and preventative strategies.